FINITE ELEMENT ANALYTICAL METHOD FOR NUMERICAL CONTROL MACHINE TOOL STRUCTURE - HU DongFang; ZHANG WenBo (Jixie qiangdu)
when using the software of the finite element analysis for a numerical control machine tool,the key issue is to obtain a good result precision. The conventional structural analyses put interest in a single part of machinery and ignore the influences of accurance and reliability acted machine parts of cutting force,gravity and other external load between applied force and constrained assembly relationship for every part under actral working conditionst. The assembly relationship of a column milling ＆ tooling machinery was analyzed,the contact and node coordinate coupling was set in relevant structure position. the relationship of every key part of the machine tools was transferred to the finite element model and more closer to the actral working conditions. With comparing the result of finite element methods to the field test,the comparative result shows this analytical method that consider the assembly relationship between every parts can ensure the method feasible and reliable.